2008
DOI: 10.1007/s10163-007-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnCl2 impregnation ratio on pore structure of activated carbons prepared from cattle manure compost: application of N2 adsorption-desorption isotherms

Abstract: Activated carbons were prepared from cattle manure compost (CMC) by ZnCl 2 activation with various ZnCl 2 /CMC mass ratios. Based on the N 2 adsorptiondesorption isotherms, mathematical models including the Dubinin-Radushkevich (DR) equation, the α s plot, and the Horvath-Kawazoe method were used to analyze the pore structural characteristics of the prepared activated carbons. It was found that for carbons possessing both micro-and mesopores, the DR method provided a more accurate estimation than the α s metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Compared to activated carbon, biochar has a wide range of sources, including industrial waste, 7 agricultural by-products, 3,8,9 livestock manure, 10,11 sludge, etc. 12 Biochar itself has the advantages of large pores, 9,13 high surface area, 13 and rich surface functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to activated carbon, biochar has a wide range of sources, including industrial waste, 7 agricultural by-products, 3,8,9 livestock manure, 10,11 sludge, etc. 12 Biochar itself has the advantages of large pores, 9,13 high surface area, 13 and rich surface functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that increasing amount of ZnCl 2 during activation of biomass can lead to higher overall porosity, and shifting of micropore widths to higher values. 52,53 This can explain the larger pores for VRnzZ-50-630 and VRnzZ-10-630, but less so the apparent temperature-dependence of the PSD. As the size and distribution of pores formed by ZnCl 2 activation of the NH 4 Cl-stabilised VR is known principally to be driven by dehydration around ZnCl 2 and its hydrates, it is possible that at 700 °C any water associated with the ZnCl 2 crystal structure is driven off before porogenesis occurs, thus yielding smaller pores.…”
Section: Resultsmentioning
confidence: 99%
“…Fe 3 O 4 increases the heterogeneity of the adsorbent, leading to higher porosity and, consequently, a better nitrogen absorbency [ 56 ]. The isotherms’ N 2 adsorption curve indicates step condensation behaviour which also could be due to the presence of microporous structures in the beads [ 57 ].…”
Section: Resultsmentioning
confidence: 99%